Associative approaches to lexical development - Plunkett, K (Wiley, 2016)
An associative approach to lexical acquisition assumes that the principles of associative learning are adequate to account for the representations and processes underlying the mature use of words. This chapter considers whether cognitive machinery is needed to explain early lexical development by entertaining the possibility that associative mechanisms are sufficient to account for some of the important findings in the field. Three such constraints have proved particularly influential in informing cognitive approaches to lexical development, such as whole object constraint (WOC), taxonomic constraint (TC), and mutual exclusivity (ME). The WOC strikes at the heart of the Quinean conundrum, solving it at a stroke by stipulating that toddlers interpret novel labels as names for whole objects. The TC assumes that “labels refer to objects of like kind rather than objects that are thematically related”. The mechanism underlying ME might guide attention toward the name-unknown object, but only subsequently might this lead to learning.